Perilaku Petani terhadap Teknologi Pengolahan Pakan Ternak Fermentasi Jerami Padi (Kasus pada Simantri 222 Gapoktan Sriasih di Desa Pohsanten, Kecamatan Mendoyo, Kabupaten Jembrana) - KARNAWAN, I PUTU JUNI; SUDARTA, WAYAN; SUARDI, I DEWA PUTU OKA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2017)
The Behavior of Farmers toward Animal Feed Processing Technology of Rice Straw Fermentation (A Case at Simantri 222 of Farmers’ Group of Sriasih in Pohsanten Village, SubDistrict of Mendoyo, Regency of Jembrana.) By the development of the agricultural sector in the Province of Bali, the Bali Provincial Government has implemented an integrated agriculture system, better known as Simantri whose aim is to support the development of farming in an integrated manner to the local potentials by increasing incomes as one of the supporting government programs to reduce poverty, integrating farming crops and cattle, and initiating the development of integrated sustainable agriculture in order to increase revenue. The purpose of the study was to determine the level of farmers’ behavior in Simantri 222 towards the development of fermented animal feed processing technology. The scope of this research was the study of the behavior (knowledge, attitudes, skills) of farmers toward the fermented feed processing technologies implemented by the members of Simantri 222 of farmers’ group of Sriasih of Pohsanten Village, Mendoyo Sub-District of Jembrana Regency. This study used qualitative descriptive analysis. The results showed that the behavior of members of Simantri on the fermented animal feed processing technologies found at Simantri 222 was classified as good category, with the score of knowledge of 3.93, while the score of attitude of 3.97 and the score of application of 4.16. Of the three components of behaviors (knowledge, attitude, and skills), it can be concluded that the behavior of farmers was classified as good category, by score of 4.02. For improving the behavior of members Simantri 222 of fermented animal feed processing, to be very well expected that extension can provide re-training in order for members to better understand the technology Simantri given.
Keywords: behavior of farmers; fermented; Simantri